Study of aerodynamics of a two-bladed wind turbine with porous-surfaced cylindrical blades - Sakipova, S.E.; Tanasheva, N.K.; Kussaiynova, A.K. (Publishing House of the KarSU named after E.A.Buketov, 2017)
The article discusses the study results of the aerodynamic characteristics of a two-bladed wind turbine with rotating cylinders under various airflow conditions. A two-bladed wind turbine model with porous-surfaced cylindrical blades of constant cross section was developed and made. The characteristics of the experimental model and the measurement technique are briefly described. The results of aerodynamic tests of the wind turbine model under different airflow conditions are presented. Dependences of the lifting force, drag force and traction force on airflow rate are obtained. Determinate variations in the aerodynamic forces of the model of a two-bladed wind turbine with porous-surfaced cylindrical blades with increasing incident airflow rate correspond to the physical airflow pattern.
Keywords: wind turbine; aerodynamics; rotating cylinder; drag force; traction force; porous surface